(untitled) (Research, Society and Development, 2020)
This work seeks to understand how the formal literacy process of girls took place in São Bernardo das Russas-CE. Also part of our reflections is the religious educational action and the methodological proposals that inserted these girls in the world of the first letters in the 1930s. The Patronato Coração Imaculado de Maria began its religious and pedagogical work in 1937, in the heart of the Estado Novo. That school was the first to teach girls in Russas until then. In this sense, we aim to discuss the educational activities of the Sisters of the Congregação Cordimariana to whom the aforementioned school was given. We will seek to analyze the marks of the local, regional and national political context with regard to the model of society expressed in the educational projects of that time. In order to carry out this research, the methodology employed is based on bibliographic analyzes, which helps us to situate the theme of this study within the theoretical and conceptual framework of the History of Literacy in Ceará and History of Education, with the use of Oral History procedures as methodological support as memory reports. The hemerographic sources, such as the newspapers, present themselves as indispensable sources to the understanding of the universe of the educational abandonment to which Vale do Jaguaribe region was exposed, and especially the girls in the beginning of the 20th century.